2003
DOI: 10.1002/ddr.10298
|View full text |Cite
|
Sign up to set email alerts
|

Brain uptake of radiolabeled N‐oleoyl‐dopamine in the rat

Abstract: N-acyl-dopamines are a novel class of biologically active lipids that have recently been identified in the brain and have the potential to interact with neural signaling pathways. This study seeks to determine the ability of N-oleoyl-dopamine, a synthetic amide of oleic acid and dopamine, to cross the blood brain barrier. We determined the tissue content of radioactivity in selected brain regions, in a shortrun study design, following injections of [ 3 H]N-oleoyl-dopamine (0.4 mCi) into the internal carotid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…We have already successfully applied this approach for the radio-labeling of dopamides and we concluded that N-oleoyl-dopamine (the analogue of compounds 9c, and 9e-9f) had an appreciable ability to cross the blood-brain barrier (Pokorski et al, 2003). Our study suggested a potential pharmacological role for exogenously delivered selected dopamides in helping regulate the brain function and that N-oleoyl-dopamine might enhance the normally limited dopamine transport into the brain, which would be of therapeutic potential in the pathological states characterized by deranged brain neurotransmitter profile.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have already successfully applied this approach for the radio-labeling of dopamides and we concluded that N-oleoyl-dopamine (the analogue of compounds 9c, and 9e-9f) had an appreciable ability to cross the blood-brain barrier (Pokorski et al, 2003). Our study suggested a potential pharmacological role for exogenously delivered selected dopamides in helping regulate the brain function and that N-oleoyl-dopamine might enhance the normally limited dopamine transport into the brain, which would be of therapeutic potential in the pathological states characterized by deranged brain neurotransmitter profile.…”
Section: Resultsmentioning
confidence: 97%
“…The possibility that neurotransmitters exist in N-acylated forms was postulated by Matysiak already in 1998 (Pokorski andMatysiak, 1998). Pokorski and Czarnocki have recently shown on the basis of radioactive labeling that N-acyldopamines can easily move through the brain-blood barrier and may therefore play role as pro-drugs capable to slowrelease of dopamine within the brain (Pokorski et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…With that assumption in mind, in the present study we used the concentrations of OLDA of 2.2 mM (1.1 µmol/0.5 ml) in in vitro part and 6 mM (12.0 µmol/2 ml) in ex vivo part, which were non-physiologically high. These concentrations were based on the findings of Pokorski et al [5] that one micromole of OLDA (the approximate amount used in vitro in the present study) is the presumed quantity of the compound to be present in 1 g of rat brain tissue after systemic administration of 40 mg/kg OLDA at a penetration yield of 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Although OLDA is present endogenously in mammalian brain [4] , neither its metabolism nor the biological role has been well explored. Exogenously applied OLDA is taken up by both central and peripheral neural tissues [5] , [6] . OLDA seems to be more stable in vitro than dopamine proper is [7] , [8] and some of OLDA major bioactivities noted in the experimental studies, such as enhancement of locomotor activity [7] or lowering the reserpine-induced muscle rigidity [9] , are mediated via the dopamine pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A delayed action of L-DOPA is not surprising, taking into account the fact that it should be enzymatically converted to DA before it produces a therapeutic effect. OLDA, a lipid derivative of DA, is able to cross the blood-brain barrier as an integral compound (13), which suggests that it might serve as a potential pro-drug or a DA carrier into the brain (1). An in vitro study with other N-acyl-dopamides, which exhibit weaker bioactivities than OLDA, shows that these compounds resist hydrolysis by the fatty-acid amide hydrolase and the DA moiety coupled to a free fatty acid apparently loses its affinity for D1 and D2 receptors (12).…”
Section: Discussionmentioning
confidence: 99%